Pelatihan Kemampuan Berhitung Matematika Siswa dengan Metode Jarimatika di Kelas V SDN Pontang Legon 2 - Nisa Aula Nurussalamah; Nazwa Guseynova Kamila; Cashia Anastasya; Ahmad Rayhan (Yayasan Literasi Sains Indonesia, 2023)
This service activity is motivated by the large number of elementary school students who have not mastered and are able to do math easily, quickly and happily. Therefore, efforts are needed to increase students' interest and enthusiasm in calculating mathematics quickly, especially in the arithmetic operations of addition, subtraction, and multiplication. This community service activity is carried out in the form of numeracy skills training using the jarimatics method which can attract students' interest in calculating quickly and precisely and improve the concept of counting because the learning process is interesting and fun so that it can sharpen children's psychomotor skills by using their fingers. . This training activity used the lecture and demonstration method, which lasted for one day with 25 grade V students at SDN Pontang Legon 2, Pontang Legon Village, Tirtayasa District, Serang District, Banten Province. From this training activity, students at SDN Pontang Legon 2 are able to master arithmetic using the easy, fast and fun way of learning in every learning process.